026 TRENDS IN IN-HOSPITAL TREATMENTS, INCLUDING REVASCULARISATION, FOLLOWING ACUTE MYOCARDIAL INFARCTION, 2003–2010: A MULTI-LEVEL AND RELATIVE SURVIVAL ANALYSIS FOR THE NATIONAL INSTITUTE FOR CARDIOVASCULAR OUTCOMES RESEARCH (NICOR). (24th May 2013) - Gale, C P; Allan, V; Cattle, B A; Hall, A S; West, R M; Timmis, A; Gray, H H; Deanfield, J E; Fox, K A A; Feltbower, R
Abstract : Background: It is not known how survival has changed over time for patients who do and do not receive an early invasive strategy for the management of AMI. Methods: Accelerated failure-time and relative survival analyses of 583 466 patients recorded in the Myocardial Ischaemia National Audit Project (MINAP) with AMI stratified by acute reperfusion treatment (thrombolysis or primary percutaneous coronary intervention (PPCI)) for STEMI and coronary angiography for NSTEMI. Results: Table 1 shows the patient characteristics by STEMI and NSTEMI phenotype. Figure 1 shows that survival improved significantly over time for STEMI patients who received acute reperfusion therapy (Time Ratio (TR) 1.47, 95% CI 1.22 to 2.78), and was stable for those who did not (TR 1.02, 95% CI 0.85 to 1.22). Whilst there were significant improvements in survival for NSTEMI patients who underwent coronary angiography (TR 1.39, 95% CI 1.18 to 1.62), there was a significant decline for those who did not (TR 0.70, 95% CI 0.65 to 0.75) (figure 2 ). Patients without acute reperfusion therapy or coronary angiography had a greater number of co-morbidities, but the use of secondary prevention medications were comparable to patients who received emergency reperfusion therapy or coronary angiography. There was a highly significant hospital-level survival effect, with lower crude mortality rates within hospitals with higher use of coronary angiography and PPCI. Conclusions: Survival to 6-months after AMI is high, and has improved. Whilst survival estimates for STEMI patients who did not receive emergency reperfusion were stable, it worsened for NSTEMI patients not receiving coronary angiography. Hospital treatments (including revascularisation), and their variation in use, are associated with longer-term survival.